Ethnic differences in pain, function, and catastrophizing in South Florida adults with knee osteoarthritis - Daniel Quintero; Jacob Jahn; Jean Jose; Eric Kholodovsky; Levi M. Travis; Joseph P. Costello II; Olivia Perez; Alberto J. Caban-Martinez; Thomas M. Best (PLoS ONE, 2025)
Objective Ethnicity is associated with varying reporting of pain, coping mechanisms, and disease severity in patients with knee osteoarthritis (KOA). However, few studies have evaluated its importance in ethnicity, particularly the Hispanic population. This study compares pain intensity (VAS), function (WOMAC), and pain catastrophizing (PCS) between Hispanic (HP) and non-Hispanic White patients (NHWP) stratified by socio-economic status (SES) and osteoarthritis radiographic K-L grade. Methods A cross-sectional study of patients from a tertiary care clinic between July 2021 and December 2022 was performed. Patients with knee pain, radiographs, and doctor-diagnosis of KOA completed questionnaires in English or Spanish. Descriptive statistics characterized demographic differences between NHWP and HP in VAS, WOMAC, and PCS. Two one-way analyses of variance evaluated the effect of both ethnicity and sex, with subgroup analyses stratifying by K-L grade. Multivariate general linear models assessed primary outcomes while controlling for confounders. Results A total of 195 subjects (HP = 145, NHWP = 50) were included. HP exhibited higher VAS, PCS, and WOMAC scores compared to NHWP. PCS was higher in HP (p = 0.004, mean = 8.89) than NHWP (mean = 4.58), as was VAS (p < 0.001, mean = 4.28 vs. 2.74) and WOMAC (p = 0.029, mean = 27.86 vs. 21.58). These differences remained when controlled for NSES and K-L grade. Stratifying by sex and comparing primary outcomes between HP and NHWP, male HP had greater VAS (p = .021, mean = 3.83 vs. 2.42) and PCS (p = .008, mean = 8.83 vs. 3.35), while female HP had greater VAS (p = .019, mean = 4.62 vs. 3.08) and nonsignificantly greater PCS (p = .164, mean = 8.94 vs. 5.92). Conclusion HP with KOA reported greater pain severity, functional limitation, and PCS. compared with NHWP, even after adjusting for NSES and K-L grade. Our findings expand on previous reports by including a larger number of HP and analyzing the role of sex, impact of socioeconomic status, and influence of radiographic severity on patient symptoms.